Saint Lucia. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Saint Lucia IICAs Delegation contributed to update the plant and animal health regulations as part of the modernization of the national sanitary and phytosanitary (SPS) system through an extensive consultative process with public and private sector stakeholders under the 11th European Development Fund Sanitary and Phytosanitary Measures Project. In addition, It supported the local and regional apiculture industry through capacity building and events such as a virtual session on organic control of varroa mite, the local celebration of International Pollinators Day, and the hosting of the Regional Congress of Beekeepers. Also, it assisted local MSMEs in improving their trade planning and negotiations and supported the development of an integrated and regenerative model for compost and biofertilizer production, mushroom production, and value-addition to cocoa. Other achievements included the revitalization of the Saint Lucia Agricultural Forum for Youth and the establishment of The Mushroom Collective, an association for promoting participation and investment in mushroom production. IICA also provided training and institutional strengthening for the operationalizing of a green business using ecosystem-based adaptation principles.